A percepção dos peritos criminais federais sobre as competências necessárias aos cargos de chefia: o caso das unidades descentralizadas de Perícia Criminal Federal - Souza, Julio Coelho Ferreira de (2013)
This study aims to understand the perception that the Federal Forensic Experts from the Department of Federal Police boast about the skills needed for those who occupy positions of leadership. The sample consists of Federal Forensic Experts under ten years of experience in the position of expert, from the 2004 tender and crowded especially in decentralized units located in inner cities in Brazil as well as in some of the northern capital. The study has an exploratory and descriptive, whose means were adopted to field research, documentation, literature and case study. The sample consisted of 33 Federal Forensic Experts who are or have the leading position in the units of the Federal Forensic Units. The research was conducted through a questionnaire consisting of 75 questions and sent via electronic mail to the respondents, with 54 questions related to technical and behavioral competencies derived from a mapping of skills held by the Federal Police Department focused on all servers. Once validated data were analyzed using descriptive statistics, not being used to factor analysis because the data extracted from the answers are insufficient in number for this technique. The results showed that the technical and behavioral skills most relevant are associated with systemic view, resource use and management activities, managing the day-to-day knowledge and the interests, needs and allocation of Federal Forensic Expertise. The results indicate that there is a gap between the strategic planning of the Scientific Technical Directorate and General Directorate of the Federal Police Department, suggesting that the flattening of organizational culture is needed in the institution. The criteria for a Federal Forensic Expert assume a position of leadership does not take into account the individual's profile. The criterion adopted, is predominantly convenience or seniority. There, in the course of training or during his tenure, going back to the area of management skills. At the end of the study are pointed out the limitations of the research.